The Effect of Sports Science Students’ Social Media Addictions on Redundant Purchasing Behavior - Doganer, Seckin; Akoglu, Halil Erdem (Asian Journal of Education and Training, 2020)
The aim of this research is to determine the causes of redundant purchasing behavior of university students and the effects of social media usage on redundant purchasing behavior. Quantitative research method is used in the research and relational screening model is preferred. "Social media addiction" and "sustainable consumption behavior scale" were used in the research. The research group consists of 221 men and 181 women in total, 402 students who studying at Ankara University Faculty of Sport Sciences. In the research, the pre-control of the data was provided and the distribution of normality was examined primarily. From the parametric tests to the data that appear to provide normal distribution; t-Test, One-Way Anova and Correlation tests were applied. According to the findings, it was found that women had a high redundant purchase behavior compared to men. It has been determined that the use of credit cards increases redundant purchases in students and affects daily life. It was observed that unrestrained shopping perception is high among students who are not licensed athletes. As the high income students' redundant purchasing behavior is high, as the time spent on social media increases, social media addiction and redundant purchasing behavior also increase. As a conclusion, it is observed that consumption behaviors are closely related to social media addiction and sustainable consumption behaviors. The suggestions of the findings obtained were tried to be given in the research, including future research.